AGILE METHODS AND GSD: THE WRONG SOLUTION TO AN OLD BUT REAL PROBLEM. (Communications of the ACM, 2006)
The article discusses agile methods in global software development (GSD), which the author argues are not suitable for the myriad of problems associated with GSD. The author claims that the chronic problems in software development cannot be fixed using agile development methods because standardization in software documentation, while time consuming, can help to alleviate some of the challenges encountered in GSD, particularly those caused by poor communication. The author argues that GSD efforts have actually exacerbated the communication problems which have long been present in the software development industry.